(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
This article presents the results of the study of the effect of microelements on the leaf area, plant height formation and yield of cotton in the conditions of the gray soil of the Zarafshan Valley. The optimal rate of using microelements had a positive effect on the leaf area and dry mass of cotton plants.The highest result was observed when N200P140K100 +KUPRUMHITE+NANOSEREBRO kg/ha was applied with mineral fertilizer.